2020
DOI: 10.1177/2165079920934000
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Virtual Reality–Generated Construction Environments at Different Heights on Postural Stability and Fall Risk

Abstract: Background Falls due to postural instability are common in construction environments especially from a height. The purpose of the study was to investigate the impact of virtual reality (VR)-generated environments at different virtual heights on postural stability. Methods Nineteen adults were analyzed for postural stability, tested in real (No VR) environment and in three VR environments, randomly assigned, at virtual heights of 0 ft. (VR0), 40 ft. (VR40), and 120 ft. (VR120). Postural stability was quantified… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(19 citation statements)
references
References 29 publications
1
16
1
Order By: Relevance
“…Thus, the increased body sway velocity in high fear participants suggests that they may not be able to use sensory feedback adequately when exposed to heights. We also observed that the magnitude of body sway decreased with ascending virtual height (similarly in both groups), which is in line with some of the previous reports ( Cleworth et al, 2012 ; Raffegeau et al, 2020 ), but not others ( Simeonov et al, 2005 ; Wuehr et al, 2019 ; Chander et al, 2021 ). The reasons for such inconsistent findings across the studies are not clear.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Thus, the increased body sway velocity in high fear participants suggests that they may not be able to use sensory feedback adequately when exposed to heights. We also observed that the magnitude of body sway decreased with ascending virtual height (similarly in both groups), which is in line with some of the previous reports ( Cleworth et al, 2012 ; Raffegeau et al, 2020 ), but not others ( Simeonov et al, 2005 ; Wuehr et al, 2019 ; Chander et al, 2021 ). The reasons for such inconsistent findings across the studies are not clear.…”
Section: Discussionsupporting
confidence: 93%
“…Second, also inconsistent are the reports on the effect of virtual height exposure on postural balance. While Cleworth et al (2012) found that body sway magnitude decreased during exposure to height in VR, several other studies reported the opposite effect, i.e., an increase in the magnitude of body sway (Wuehr et al, 2019;Raffegeau et al, 2020;Chander et al, 2021). Furthermore, it has been reported that postural reactions to simulated height are independent of individual height intolerance and the elicited fear (Wuehr et al, 2019), in contrast to real height exposure when postural adjustments were related to individual fear and anxiety levels (Davis et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…The increased postural demands in the tandem and one-leg standing tasks increased the sway parameters in both VEs, but only a slight difference was observed between being in a photorealistic and a blank scene. The richness and fidelity help to increase level of presence in VR [14,19], but it may not be the most important contributing factor for postural stabilization according to our observation in a BS condition. The role of visual targeting in the VE was not highlighted in past studies and might have contributed to the effects of scene design.…”
Section: Discussionmentioning
confidence: 63%
“…Dynamic visual stimuli can be created by VR as a perturbation, which significantly influences postural control. For example, an increased center of pressure (COP) displacement or body sway is observed in response to perturbed visual scenes in VR, including moving dots, moving walls, rotating optokinetic drums or simulated movies [17][18][19][20]. However, these visual perturbations have increased risks of cybersickness or falls [17], and are therefore mostly used in postural assessment, but not in VR-based balance training.…”
Section: Introductionmentioning
confidence: 99%
“…An analysis of the student's evaluation of this technology showed the use of VR positively impacted the students learning and understanding of the construction process. VR has also been utilized for various other safety-related applications, such as actively monitoring the site and informing laborers about the site's likely dangers (Cheng and Teizer, 2013), transferring the safety information to laborers (Guo et al, 2012), and height safety training (Chander et al, 2019(Chander et al, , 2021. More recently, Zhoa and Lucas (2015) developed a VR platform to educate workers on electrical power hazards.…”
Section: Related Workmentioning
confidence: 99%